The Effects of Corpora Luteal Number on Serum Progesterone and Estradiol of Ewes During Luteal Phase of Estrous Cycle and Pregnancy - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Two experiments were conducted to study the effects of corpora luteal number on maternal senint concentrations of progesterone and cstradiol during luteal phase of estrous cycle and pregria.ncy. The experimental ewes Wer0 injected twice with I ml PGF2 to destroy previously existed corpora lutea The number of corpora lutca was counted by laparoscopy 5 days after the onset of estrous cycle. Blood samples were collected weekly during the estrous cycle and biweekly during pregnancy for lionnone analyses using raclionnuatinoassay, Simple correlation was used to determine the relationship between the number of corpora lutea and pi ogesterone or estradiol concentrations. Progesterone concentrations increased with the number of corpora linca dui tug the lineal phase of estrous cycle (P